The effect of VEGF, ET-1 and TGF-β1 levels in peritoneal dialysis effluent on peritoneal solute transport function - Han, Xinxuan; Li, Long; Yu, Xiangjiang; Jiang, Yan; Li, Feifei; Luo, Shixi; Zeng, Xingxin; Zhang, Ming (Frontiers in Medicine, 2025)
ObjectiveThis study aims to assess the impact of Vascular endothelial growth factor (VEGF), Endothelin-1 (ET-1), and Transforming growth factor-β1 (TGF-β1) levels in peritoneal dialysis effluent on peritoneal solute transport function.MethodsWe included 450 patients from four hospitals, spanning from January 2016 to January 2018. Patients were categorized into low-transport (D/Pcr ≤ 0.65) and high-transport groups (D/Pcr > 0.65) based on solute transport rates. We compared the effluent levels of VEGF, ET-1, and TGF-β1 between the groups, employed Pearson’s correlation for analysis, and used multivariate logistic regression to identify independent factors influencing solute transport.ResultsVEGF and TGF-β1 levels were significantly higher in the high-transport group (p < 0.05), showing a positive correlation with solute transport function (r = 0.721 and 0.539 respectively, p < 0.05). ET-1 levels showed no significant difference between the groups. VEGF and TGF-β1 were identified as significant independent factors affecting solute transport (OR = 3.438 and 3.684, p < 0.05). ROC curve analysis highlighted the predictive value of VEGF and TGF-β1 for solute transport function. Kaplan–Meier and COX regression analyses indicated that high transport was associated with lower survival rates, with VEGF and TGF-β1 serving as independent risk factors for mortality (RR = 3.442 and 3.550, p < 0.05).ConclusionVEGF and TGF-β1 levels in peritoneal dialysis effluent are strongly correlated with solute transport function and serve as significant predictors of patient outcomes.